2020
DOI: 10.1371/journal.pntd.0008222
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of leptospiral antibodies in rodents from riverside communities of Santa Fe, Argentina

Abstract: Background Leptospirosis is a zoonotic disease that can be transmitted by contact with the urine of infected mammals. Rodents play a mayor role in the transmission of leptospires to humans. The province of Santa Fe reports the greatest number of cases in Argentina. Yet, in this region, there are still knowledge gaps regarding the diversity of rodent species that may be hosts of pathogenic leptospires. The aims of this study were to evaluate the presence of leptospiral antibodies in rodents from three riverside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…S. aquaticus can be found in semi-aquatic habitats, such as swamps, water courses, or flooded areas with low vegetation of the argentine ecoregions of Humid Chaco, Paraná flooded savanna, Espinal, Pampas and Iberá, as well as in western Uruguay, southern Paraguay and southern Brazil [29-31] (Fig 2). This species was also found to be a reservoir of pathogenic leptospires in areas of the Paraná flooded savanna from the provinces of Santa Fe and Buenos Aires [32, 14, 15]. The knowledge gaps on lack of evidence about the role of some rodent species as reservoirs hosts of these hantaviruses, favors the risk of orthohantavirus transmission and hinders HPS prevention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. aquaticus can be found in semi-aquatic habitats, such as swamps, water courses, or flooded areas with low vegetation of the argentine ecoregions of Humid Chaco, Paraná flooded savanna, Espinal, Pampas and Iberá, as well as in western Uruguay, southern Paraguay and southern Brazil [29-31] (Fig 2). This species was also found to be a reservoir of pathogenic leptospires in areas of the Paraná flooded savanna from the provinces of Santa Fe and Buenos Aires [32, 14, 15]. The knowledge gaps on lack of evidence about the role of some rodent species as reservoirs hosts of these hantaviruses, favors the risk of orthohantavirus transmission and hinders HPS prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on the study protocol can be found in Ricardo et al . [14, 15]. Briefly, each community was splitted into 3 study sites based on their level of human disturbance, and 25 trapping stations (consisting of a Sherman trap and a live-cage trap) were set per site during 3 consecutive nights.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We placed 25 trapping stations (consisting of a Sherman trap and a live-cage trap) per site during 3 consecutive nights. Traps were placed on vacant lots, road edges, river banks, and houses peridomicile at regular intervals of approximately 10 m. Detailed information on the study protocol can be found in Ricardo et al [ 14 , 15 ]. Blood samples were collected by cardiac puncture and tissue samples by systemic necropsy.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the actual value to be used in the model, a rodent population study could be performed to quantify what percentage is actually infected, as the one carried out by Ricardo et al (2020). On the other hand, controlling such population and minimizing the contact with the human population would be effective measures to reduce the impact of a leptospirosis outbreak, just to mention an example.…”
Section: Sensitivity Analysismentioning
confidence: 99%